Social isolation and the speed of covid-19 cases: transmission prevention measure - Silva, Fábio Castagna da (2021)
ABSTRACTObjective: To evaluate the social isolation index and the speed of new cases of Covid-19 in Brazil.Method: Quantitative, documentary, descriptive ecological, using secondary data, comparing the period from March 14 to May 1, 2020, carried out with the 27 Brazilian federative units, characterizing the study population. The data were analyzed through analysis descriptive statistics, using the Statistical Package for the Social Sciences-SPSS® software, evaluating the correlation between the social isolation index and the number of new cases of Covid-19, using Pearson's correlation coefficient.Results: The increase in Covid-19 cases is exponential. There was a significant, negative correlation regarding the social isolation index and the speed of the number of new cases by Pearson's coefficient, which means that as the first increases, the second decreases.Conclusion: Social isolation measures have significant effects on the rate of coronavirus infection in the population.Keywords: Coronavirus infections. Coronavírus. Social isolation. Communicable diseases. Public health. Communicable disease control.